Exporting out of agriculture: The impact of WTO accession on structural transformation in China - Erten, Bilge; Leight, Jessica (MIT Press, 2021)
This paper analyzes the effect of China's accession to the World Trade Organization in 2001 on structural transformation at the local level, exploiting cross-sectional variation in tariff uncertainty faced by county economies pre-2001. Using a new panel of 1,800 Chinese counties from 1996 to 2013, we find that counties more exposed to the reduction in tariff uncertainty postaccession are characterized by increased exports and foreign direct investment, shrinking agricultural sectors, expanding secondary sectors, and higher total and per capita GDP. In addition, when labor substitutes from nonagricultural to agricultural production in counties exposed to positive trade shocks, agricultural output declines.